Examining Colleges of Education Science Tutors’ Practices of Differentiated Instructions: A Study of Colleges of Education in the Volta Region - Agbeko, David Tsitu; Mensah, Kofi; Gyampoh, Alexander Obiri; Amoako, Stephen Kwame; Harvey, Florence (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
The study aimed to examine colleges of education science tutors’ practices of differentiated instruction in the Volta Region of Ghana. The study employed explanatory sequential design. The participants were 32 science tutors from Colleges of Education in the Volta Region of Ghana, who were purposively selected based on having direct instructional contacts with students all the time and their teaching experiences within and outside colleges. Questionnaire, Rating Scale, and Interview were used to collect data. It was found that science tutors have different knowledge on content, learning style, learner interest, learner diversity, process, product, and lesson planning. The findings also revealed that majority (80%) of science tutors who did not differentiate instruction in their classrooms have the knowledge of differentiated instruction but their failure to make use of DI was due to scarcity of time, complex nature of DI, high level of workload. The results also revealed that, majority (80%) of the science tutors did not use their assessment feedback to guide their instruction. These science tutors said marking schemes were always given to the students for self-correction. The results from classroom observation showed that these tutors do not teach to meet the diverse needs of learners. Majority of the participants still hold to traditional classroom teaching strategies based on one size-fits-all approach which proved to be ineffective. The study recommended that mentoring universities should organize workshops on the differentiated instructional for tutors and mount course in DI for student teachers.
Keywords: Practices; Differentiated instruction; Science; Tutors; Traditional classroom